Integrasi Nilai-Nilai Islam dalam Pembelajaran Kimia: Pendekatan Kontekstual di Program Studi Pendidikan Kimia Universitas Islam Sumatera Utara - Siregar, Wildawani; Rizaldi, Rachmat; Hasanah S., Uswatun (Medan Resource Center, 2025)
This study aims to examine how Islamic values are integrated into chemistry learning through a contextual approach at the Chemistry Education Study Program of Universitas Islam Sumatera Utara. Using a qualitative case study method, data were collected through interviews, classroom observations, and document analysis involving lecturers, students, and program administrators. The analysis focuses on how religious values are embedded within the learning process. Integration occurs through various strategies, including the use of instructional materials that reference Quranic verses and hadiths, contextual case studies with real-life relevance, group-based reflections, and character-oriented assessments. A contextual learning approach—particularly problem-based learning and the use of Islamic-themed teaching media—is employed to bridge scientific concepts with students’ religious and everyday experiences. Findings indicate that this model encourages student engagement and supports the internalization of values such as honesty, social responsibility, and care for the environment. The integration of Islamic values is not merely additive but becomes an integral part of students’ cognitive and affective learning experiences. This study contributes to the discourse on faith-based education by offering a model for combining religious and scientific knowledge in higher education. It underscores the potential of contextual learning to foster both academic understanding and character development, in line with Indonesia’s educational vision that promotes intellectual achievement alongside moral and spiritual formation.